Investigation of the properties of nanostructured Li-doped NiO films using the modified spray pyrolysis method - Chia-Ching, Wu (Springer, 2013)
The lithium-doped nickel oxide (L-NiO) films were synthetized using the modified spray pyrolysis method with a two-step grown process. By observing the spectra of X-ray photoemission spectroscopy of L-NiO films, the intensity of Ni 2p(3/2) peak of Ni(3+) bonding state increases with increasing Li concentration that causes the decrease of transparency and resistivity. The L-NiO films with optimum characteristics were obtained at Li = 8 at%, where a p-type resistivity of 4.1 × 10(−1) Ω cm and optical transparency above 76% in the visible region are achieved.